Airborne exposures associated with the typical use of an aerosol brake cleaner during vehicle repair work. Issue 7 (3rd July 2018) - Fries, Michael; Williams, Pamela R.D.; Ovesen, Jerald; Maier, Andrew
ABSTRACT: Many petroleum-based products are used for degreasing and cleaning purposes during vehicle maintenance and repairs. Although prior studies have evaluated chemical exposures associated with this type of work, most of these have focused on gasoline and exhaust emissions, with few samples collected solely during the use of an aerosol cleaning product. In this case study, we assess the type of airborne exposures that would be expected from the typical use of an aerosol brake cleaner during vehicle repair work. Eight exposure scenarios were evaluated over a 2-day study in which the benzene content of the brake cleaner and potential for dilution ventilation and air flow varied. Both short-term (15 min) and task-based (≥1 hr) charcoal tube samples were collected in the breathing zone and adjacent work area and analyzed for total hydrocarbons (THCs), toluene, and benzene. The majority of personal (N = 48) and area (N = 47) samples had detectable levels of THC and toluene, but no detections of benzene were found. For the personal short-term samples, average airborne concentrations ranged from 3.1–61.5 ppm (13.8–217.5 mg/m 3 ) for THC and 2.2–44.0 ppm (8.2–162.5 mg/m 3 ) for toluene, depending on the scenario. Compared to the personal short-term samples, average concentrations were generally 2–3 times lower for the personal task-based samples and 2–5 times lower for the area short-term samples. The highest exposures occurred when the garage bay doors were closed, floor fan was turned off, or greatest amount of brake cleaner was used. These findings add to the limited dataset on this topic and can be used to bound or approximate worker or consumer exposures from use of aerosol cleaning products with similar compositions and use patterns.